Islamization and The Crisis Of Educational Dualism (Revisiting al-Faruqi’s Thought in the Context of Contemporary Muslim Societies) - Susilawati Susilawati; Eliana Siregar; Rahmad Tri Hadi; Yahya Ibrahim (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The crisis of educational dualism based on the distinction of religious and secular sciences is one of the most urgent problems in the context of modern Islamic education. This problem leads to the epistemological division in Muslim communities and contributes to poor integration of ethical, religious, and scientific components in the process of educating students. This paper seeks to explore the ideas of Ismail Raji al-Faruqi on Islamization and integration of knowledge with the purpose of solving the problem of educational dualism. To conduct this study, the authors used a qualitative research design with the application of descriptive and contextual approaches. The data was gathered by means of documentation, including major works of al-Faruqi and related to Islamic educational reforms. The results demonstrate that educational dualism emerges as a result of colonial and secular educational traditions in separating religion and science. As a solution to the problem of educational dualism, al-Faruqi offers tawḥīd as a basis of knowledge that brings together all spheres, including religion, science, ethics, and others.